STUDI INTERAKSI KLUSTER LOGAM DENGAN MOLEKUL N2 DAN H2 MENGGUNAKAN METODE DENSITY FUNCTIONAL THEORY (DFT) - , SITI SUHARTATI, Dr.rer.nat. Ria Armunanto, S.Si., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Interaction study of metal clusters with N2 and H2 molecules using Density Functional Theory (DFT) method has been carried out to elucidate the pentanuclear metal cluster models, structure stability, dissosiation mechanism of N2 and H2, and interaction position of N and H atoms on metal clusters. This research is able to be used as catalyst model in synthesis of ammonia. The metal cluster studied were pentanuclear square pyramidal and trigonal bipyramidal. To obtain a good cluster model, the metal clusters (Rh, Pd, Pt, Ir, Ag and Au) were optimized using DFT based on B3LYP function. The method was carried out to obtain its lattice energies and bond lengths. Structure which has parameters in accordance with experimental data was used for the interaction model study. Lattice energy of Ag pentanuclear metal clusters showed a good agreement with experimental data. Bond length of 2.89 Ã which was observed for Ag pentanuclear metal clusters trigonal bipyramidal was higher than the square pyramidal (2.85 Ã). Structure of Ag pentanuclear metal clusters adsorbed N and H atoms were more stable than N2 and H2 molecules adsorbed on Ag pentanuclear metal clusters. Interaction of N atom with the pentanuclear of Ag cluster was in hollow position. But, on top and hollow position were for square pyramidal and bridge position for trigonal bipyramidal were observed for H atom interaction with metal cluster.